“Overdiagnosed or Misdiagnosed” – A Classic Case of Pseudohallucinations and Maladaptive Daydreaming When a Diagnosis of Adult ADHD Was Missed - Saima Jehanzeb; Amna Javaid (BJPsych Open, 2025)
Aims: Background: Attention deficit hyperactivity disorder (ADHD) can present differently in adults and often goes misdiagnosed due to overlapping symptoms. Maladaptive daydreaming may also be misdiagnosed, as it shares similarities with dissociative symptoms, depersonalization, derealization, and temporal lobe epilepsy. Jasper has identified pseudohallucinations as akin to normal perception and occurring in the inner subjective space. Adults with ADHD often experience zoning out, daydreaming, and cognitive hyperactivity, which may resemble psychosis.